Dynamic core-theoretic cooperation in a two-dimensional international environmental model - Marc Germain; Henry Tulkens; Alphonse Magnus (Fondazione Eni Enrico Mattei (FEEM), 2009)
This article deals with cooperation issues in international pollution problems in a two di- mensional dynamic framework implied by the accumulation of the pollutant and of the capital goods. Assuming that countries do reevaluate at each period the advantages to cooperate or not given the current stocks of pollutant and capital, and under the assumption that damage cost functions are linear, we define at each period of time a transfer scheme between countries, which makes cooperation better for each of them than non-cooperation. This transfer scheme is also strategically stable in the sense that it discourages partial coalitions.
Keywords: Q54; Q58; F42; F53; O21; 330; Stock Pollutant; Capital Accumulation; International Environmental Agreements; Dynamic Core Solution